(untitled) (International Research in Economics and Finance, 2019)
This essay researches the question, “To what extent did monetary policy contribute towards the recent financial crisis and subsequent recession in the US and UK?” This article begins by demonstrating monetary policy’s role in guiding the economy’s development under different economic fundamentals. Then the essay puts forward the existence of possibility that monetary policy may cause potential dangers for the economy. In the next chapter, the essay illustrates the guideline for monetary policy namely Taylor rule and economists’ arguments and explanations for the US monetary policy in the past decade. In chapter 3, this article estimates the nominal interest rates for both the US and the UK based on Taylor rule for different periods and illustrates influences of monetary policy actually taken for each country in different periods. In chapter 4, the article tests the relationship between monetary policy’s deviations from Taylor rule and financial imbalances by using the OLS method and explains results. Finally, in chapter 5, the article concludes that in some degree monetary policy’s deviations from Taylor rule prescriptions contribute to a build-up of financial imbalances.